EFECTO DEL AMORTIGUAMIENTO ANTI LAZO EN LA ESTABILIDAD LATERAL DE LOS COCHES DE UNA DUPLA FERROVIARIA ARTICULADA (Journal of Industrial and Mechanical Engineering, 2018)
Las duplas ferroviarias articuladas son vehículos modulares conformados por dos coches y una unidad motriz (UM) situada entre ellos.Cada coche exhibe la particularidad de poseer sólo un bogie en un extremo y estar apoyado sobre la UM.Todo fenómeno producido en la dinámica del sistema es magnificado por la complejidad de la distribución de la formación analizada, generando así el interés de su estudio (Knothe & Stichel, 2003; Wickens, 2003).El objetivo general es identificar el valor óptimo de amortiguamiento anti lazo situado como conexión entre ambos coches y la UM.La investigación se limitó al estudio de la estabilidad lateral, circulando a velocidad constante y bajo la excitación de un perfil aleatorio de irregularidades de vía.Abstract: The unconventional articulated railcars are modular vehicles consisting of two passenger cars and a power unit (UM) located between them.Each end module (car) has a bogie at one end and reston the UM.Every dynamic phenomena produced in the system is agnified by the complex configuration of the complete vehicle, thus generating the interest of its study (Knothe & Stichel, 2003; Wickens,2003).The general objective is to identify the optimal anti-yaw damping between both cars and the UM.The research was limited to the study of lateral stability, circulating at constant speed and using a random profile of track irregularities as wheelset input excitation.The articulated train has been characterized by a 54 state variables mathematical model, including lateral displacement, roll and yaw rotation (Shah et al., 1997).Wheel-rail contact forces were calculated using Kalker's simplified non-linear theory (Kalker, 1982).Keywords: Multibody dynamics; contact; hunting; comfort.